2001
DOI: 10.1111/j.1574-6968.2001.tb10709.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of an oral bacterium via chromosomal integration of free DNA in the presence of human saliva

Abstract: Transformation of Streptococcus gordonii DL1 by free DNA was studied in human saliva. Competent S. gordonii could be transformed in vitro with plasmid DNA that had been taken into the human mouth. Transformation also occurred with a plasmid that cannot replicate in S. gordonii, but that has a region of chromosomal homology, by integration into the bacterial chromosome, although linearised plasmid DNA gave no transformants. Linear chromosomal DNA fragments did however transform S. gordonii/Tn916 efficiently in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 33 publications
2
14
0
1
Order By: Relevance
“…Transformation of S. gordonii has been shown to occur in vitro with plasmid DNA in human saliva (104). The half-life for transforming activity of both plasmid and chromosomal DNA is only 5.7 s in saliva in the mouth, but 5.7 s is sufficient for DNA uptake and protection from salivary nucleases (105). Natural genetic transformation has been reported for many oral streptococci in planktonic cultures and occurs by induction of genetic competence through a competence-stimulating peptide (CSP) signaling system (61,97).…”
Section: In Vitromentioning
confidence: 99%
“…Transformation of S. gordonii has been shown to occur in vitro with plasmid DNA in human saliva (104). The half-life for transforming activity of both plasmid and chromosomal DNA is only 5.7 s in saliva in the mouth, but 5.7 s is sufficient for DNA uptake and protection from salivary nucleases (105). Natural genetic transformation has been reported for many oral streptococci in planktonic cultures and occurs by induction of genetic competence through a competence-stimulating peptide (CSP) signaling system (61,97).…”
Section: In Vitromentioning
confidence: 99%
“…Many oral streptococci are capable of natural transformation, which has been best studied in Streptococcus gordonii (8). Recently, it has been shown that S. gordonii can be transformed by plasmid DNA or via chromosomal integration of plasmid DNA at increased frequency in the presence of human saliva (29,30). These authors incubated plasmid DNA with human saliva or exposed the DNA to it in vivo and observed that the nucleic acid keeps its capability to transform oral streptococci in vitro.…”
mentioning
confidence: 99%
“…Enfin, l'expression du nouveau gène surviendra si le produit recombinant encodé n'est pas létal et si les séquences régulatrices incluses aux constructions génétiques pour l'étape de transgénèse sont compatibles avec la machinerie génétique de la bactérie. L'expression effective du transgène chez la bactérie hôte et ses descendants sera tributaire de facteurs variés comme la nature des séquences promotrices et amplificatrices intégrées aux constructions, l'identité des codons composant la séquence exprimée, la présence ou non d'introns dans le gène introduit et l'homologie de séquence qu'il partage avec l'ADN de l'hôte bactérien (de Vries et Wackernagel 1998;de Vries et al 2001;Mercer et al 2001;Tepfer et al 2003).…”
Section: La Persistance Des Transgènes Dans L'environnementunclassified